THE IMPACT OF THE BURDEN OF FAMILY PROBLEMS ON THE MENTAL HEALTH OF THE WIFE - rahmadani, niken; fitriani, wahidah; yeni, putri (AGENDA: Jurnal Analisis Gender dan Agama, 2024)
mental health is very important for individuals, because it affects physical, mental, and social well-being. Maintaining mental health helps individuals in managing stress, maintaining life balance, and influencing the way they think, feel, and behave. Especially in the family, family support and strong relationships also play an important role in maintaining mental health. The method carried out in this study is to use a descriptive qualitative approach by means of observation and interviews and literature review studies by taking literature results. The purpose of this method is to obtain an effective understanding and data of the problem being studied. Family burden is the level of unpleasant experiences in the family as a result of the condition of the family members, the many family burdens faced by Mrs. M have a very significant impact on the mother's mental health which causes the mother to experience psychological disorders. In the family, it is important to maintain mental health in order to produce a prosperous family. In creating a healthy mentality, it is necessary to understand the situation we are living in, with support between families, one-way communication between husband and wife and two-way communication with children.